2014
DOI: 10.1186/1471-2466-14-175
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific interstitial pneumonia: clinical associations and outcomes

Abstract: BackgroundStudies have shown that nonspecific interstitial pneumonitis (NSIP), even when initially diagnosed as an idiopathic form of the disease, might be associated with an autoimmune background that later reveals itself as an organ-specific or a systemic autoimmune disease.MethodsNSIP patients were divided into three groups. The NSIP patients who met the criteria for having a systemic autoimmune disease (SAD) were defined as the systemic autoimmune disease-associated NSIP (SAD-NSIP) group. The NSIP patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Initial daily doses ranging from 0.5 to 1 mg/kg of prednisone or 40–60 mg (in non‐weight‐based dosing) are most commonly reported . Typically, the initial dose is continued for 1 month prior to attempts at weaning .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial daily doses ranging from 0.5 to 1 mg/kg of prednisone or 40–60 mg (in non‐weight‐based dosing) are most commonly reported . Typically, the initial dose is continued for 1 month prior to attempts at weaning .…”
Section: Treatmentmentioning
confidence: 99%
“…74 Initial daily doses ranging from 0.5 to 1 mg/kg of prednisone or 40-60 mg (in non-weight-based dosing) are most commonly reported. 12,30,74,79 Typically, the initial dose is continued for 1 month prior to attempts at weaning. 12,30 Average treatment length reported by Park et al specifically for iNSIP was 17.4 ± 12.1 months.…”
Section: Treatmentmentioning
confidence: 99%
“…They suggested that sero-positivity of ANA could be an early manifestation of systemic diseases associated with a poor outcome of NSIP. Xu et al [ 19 ] also showed that systemic autoimmune disease was significantly associated with increased mortality in NSIP patients ( p = 0.023). Felicio et al [ 20 ] reported a higher production of collagen and elastic fibers in NSIP with collagen vascular disease than in iNSIP; in a cohort of 41 NSIP patients, an increase in elastic fibers >1.5% was a significant risk factor for poor outcome ( p = 0.01).…”
Section: Discussionmentioning
confidence: 97%
“…6,10,11,14,15,60 However, other symptoms including fevers and constitutional symptoms such as fatigue and weight loss may occur. 7,10,14,27,60,61 Physical examination findings such as digital clubbing (0-40%) and fine inspiratory crepitations can be present but do not discriminate NSIP from other forms of ILD. 8,10,62 A thorough clinical examination remains important, as findings such as a skin rash or Raynaud's phenomena can add impetus for the clinician to further investigate for an underlying etiology, such as an occult CTD.…”
Section: Clinical Featuresmentioning
confidence: 99%